Intensive chemotherapy with or without gemtuzumab ozogamicin in patients with NPM1-mutated acute myeloid leukaemia (AMLSG 09-09): a randomised, open-label, multicentre, phase 3 trial - Döhner, Hartmut; Weber, Daniela; Krzykalla, Julia; Fiedler, Walter; Kühn, Michael W M; Schroeder, Thomas; Mayer, Karin; Lübbert, Michael; Wattad, Mohammed; Götze, Katharina; Fransecky, Lars; Koller, Elisabeth; et al. (The lancet. Haematology, 2023)
Background - Acute myeloid leukaemia with mutated NPM1 is associated with high CD33 expression and intermediate-risk cytogenetics. The aim of this study was to evaluate intensive chemotherapy with or without the anti-CD33 antibody-drug conjugate gemtuzumab ozogamicin in participants with newly diagnosed, NPM1-mutated acute myeloid leukaemia. - Methods - This open-label, phase 3 trial was conducted at 56 hospitals in Germany and Austria. Eligible participants were 18 years or older and had newly diagnosed NPM1-mutated acute myeloid leukaemia and an Eastern Cooperative Oncology Group performance status of 0-2. Participants were randomly assigned, using age as a stratification factor (18-60 years vs >60 years), 1:1 to the two treatment groups using allocation concealment; there was no masking of participants and investigators to treatment groups. Participants received two cycles of induction therapy (idarubicin, cytarabine, and etoposide) plus all-trans retinoic acid (ATRA) followed by three consolidation cycles of high-dose cytarabine (or an intermediate dose for those older than 60 years) and ATRA, without or with gemtuzumab ozogamicin (3 mg/m2 administered intravenously on day 1 of induction cycles 1 and 2, and consolidation cycle 1). The primary endpoints were short-term event-free survival and overall survival in the intention-to-treat population (overall survival was added as a co-primary endpoint after amendment four of the protocol on Oct 13, 2013). The secondary endpoints were event-free survival with long-term follow-up, rates of complete remission, complete remission with partial haematological recovery (CRh), and complete remission with incomplete haematological recovery (CRi), cumulative incidences of relapse and death, and number of days in hospital. This trial is registered with ClinicalTrials.gov (NCT00893399) and has been completed. - Findings - Between May 12, 2010, and Sept 1, 2017, 600 participants were enrolled, of which 588 (315 women and 273 men) were randomly assigned (296 to the standard group and 292 to the gemtuzumab ozogamicin group). No difference was found in short-term event-free survival (short-term event-free survival at 6-month follow-up, 53% [95% CI 47-59] in the standard group and 58% [53-64] in the gemtuzumab ozogamicin group; hazard ratio [HR] 0·83; 95% CI 0·65-1·04; p=0·10) and overall survival between treatment groups (2-year overall survival, 69% [63-74] in the standard group and 73% [68-78] in the gemtuzumab ozogamicin group; 0·90; 0·70-1·16; p=0·43). There was no difference in complete remission or CRi rates (n=267 [90%] in the standard group vs n=251 [86%] in the gemtuzumab ozogamicin group; odds ratio [OR] 0·67; 95% CI 0·40-1·11; p=0·15) and complete remission or CRh rates (n=214 [72%] vs n=195 [67%]; OR 0·77; 0·54-1·10; p=0·18), whereas the complete remission rate was lower with gemtuzumab ozogamicin (n=172 [58%] vs n=136 [47%]; OR 0·63; 0·45-0·80; p=0·0068). Cumulative incidence of relapse was significantly reduced by gemtuzumab ozogamicin (2-year cumulative incidence of relapse, 37% [95% CI 31-43] in the standard group and 25% [20-30] in the gemtuzumab ozogamicin group; cause-specific HR 0·65; 0·49-0·86; p=0·0028), and there was no difference in the cumulative incidence of death (2-year cumulative incidence of death 6% [4-10] in the standard group and 7% [5-11] in the gemtuzumab ozogamicin group; HR 1·03; 0·59-1·81; p=0·91). There were no differences in the number of days in hospital across all cycles between treatment groups. The most common treatment-related grade 3-4 adverse events were febrile neutropenia (n=135 [47%] in the gemtuzumab ozogamicin group vs n=122 [41%] in the standard group), thrombocytopenia (n=261 [90%] vs n=265 [90%]), pneumonia (n=71 [25%] vs n=64 [22%]), sepsis (n=85 [29%] vs n=73 [25%]). Treatment-related deaths were documented in 25 participants (4%; n=8 [3%] in the standard group and n=17 [6%] in the gemtuzumab ozogamicin group), mostly due to sepsis and infections. - Interpretation - The primary endpoints of the trial of event-free survival and overall survival were not met. However, an anti-leukaemic efficacy of gemtuzumab ozogamicin in participants with NPM1-mutated acute myeloid leukaemia is shown by a significantly lower cumulative incidence of relapse rate, suggesting that the addition of gemtuzumab ozogamicin might reduce the need for salvage therapy in these participants. The results from this study provide further evidence that gemtuzumab ozogamicin should be added in the standard of care treatment in adults with NPM1-mutated acute myeloid leukaemia. - Funding - Pfizer and Amgen.
Online verfügbar 12 May 2023, Version des Artikels 3 July 2023
Gesehen am 08.12.2023